Legal Protection of Temples as Sacred Areas and Tourist Destinations in Bali - Gede Parta Wijaya; Johannes Ibrahim Kosasih (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the legal protection of temples in Bali as both sacred areas and tourist destinations. Temples hold profound ontological, epistemological, and axiological significance as spiritual centers, cultural heritage, and symbols of Balinese identity. However, the rapid growth of tourism has created tensions between sacred values and economic interests, leading to commodification and violations of customary norms. The research employs normative legal methods to analyze existing frameworks, including Law No. 10 of 2009 on Tourism, Law No. 32 of 2009 on Environmental Protection and Management, Bali Provincial Regulation No. 5 of 2020 on Cultural Tourism, and the Decree of the Central Council of Hindu Dharma Indonesia (PHDI). Findings reveal that while these instruments provide a foundation, they remain insufficient in addressing the dualism of authority between state law and customary law. Theories of legal pluralism and living law highlight the coexistence of state regulations and traditional village norms, emphasizing the need for harmonization. The study concludes that temple protection must integrate formal legal frameworks with local wisdom, ensuring sustainable tourism that respects sanctity, cultural identity, and community participation. This approach strengthens Bali’s position as both a global tourist destination and a center of spiritual civilization.